National Commitment and Tolerance as a Determinant Factor of Happiness - abdullah, Muh. Ruslan; Sabani, Akbar; Saleh Ridwan, Muhammad (Al-Amwal : Journal of Islamic Economic Law, 2024)
Purpose - This research aims to analyze National Commitment and Religious Tolerance as a factor in shaping people's happiness in Palopo City and analyze the comparison of happiness between the Muslim majority and Christian minority communities in Palopo City. Method - This research uses quantitative research using a questionnaire distributed to 200 respondents. Data were analyzed using SEM PLS. Result - The research results show that national commitment and tolerance have a positive effect on people's happiness in Palopo City. Apart from that, the results of this research show that the happiness of Christian communities is higher than that of Muslim communities in Palopo City. Implication - Policy and Governance Implications, Promoting National Commitment for Well-being: The research demonstrates that national commitment has a significant positive effect on people's happiness. This implies that government and national programs aimed at strengthening Indonesian national values (such as Pancasila and the 1945 Constitution ) should be prioritized as they are foundational to fostering religious moderation and, consequently, improving community happiness levels.